2023
DOI: 10.1111/iwj.14102
|View full text |Cite
|
Sign up to set email alerts
|

Research progress and insights on the role of ferroptosis in wound healing

Abstract: Ferroptosis is a newly discovered cell death type which is different from apoptosis, autophagy, pyroptosis as well as necrosis in the following aspects: morphology, biochemistry, gene and regulatory mechanisms. Ferroptosis is regulated by multiples of mechanisms such as system Xc À mechanism, glutathione peroxidase 4 (GPX4) mechanism, iron metabolism and lipid metabolism. Currently, ferroptosis has been revealed to be significant in wound healing such as diabetic wound, irradiated wound and ultraviolet (UV)-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Ferroptosis, distinct from apoptosis, has emerged as a promising therapeutic target for DW treatment (Bi et al, 2023;Gao et al, 2018). Network pharmacology, a field that investigates the pharmacological actions of drugs within biological networks to elucidate their connections with drug constituents, targets, and diseases, offers a novel approach to investigating the biological impacts of small molecules sourced from diverse natural origins (Luo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis, distinct from apoptosis, has emerged as a promising therapeutic target for DW treatment (Bi et al, 2023;Gao et al, 2018). Network pharmacology, a field that investigates the pharmacological actions of drugs within biological networks to elucidate their connections with drug constituents, targets, and diseases, offers a novel approach to investigating the biological impacts of small molecules sourced from diverse natural origins (Luo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous recent efforts to prevent or enhance the healing of DW, progress in addressing delayed wound healing remains sluggish. Ferroptosis, distinct from apoptosis, has emerged as a promising therapeutic target for DW treatment (Bi et al, 2023; Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation between ferroptosis and skin wounds ( 136 ). Multiple investigations have shown that the use of ferroptosis inhibitors may enhance the healing of diabetic wounds by suppressing the process of ferroptosis.…”
Section: The Molecular Mechanisms Of Healing Processmentioning
confidence: 99%
“…This process can be suppressed by ferrostatin-1. In addition, an overabundance of UV radiation may lead to a deficiency in GSH, which in turn disrupts the balance of redox reactions in the body ( Figure 4 ) ( 136 , 141 ).…”
Section: The Molecular Mechanisms Of Healing Processmentioning
confidence: 99%
“…Ferroptosis in skin cells can be induced by environmental stressors (e.g., ultraviolet radiation and air pollution) and internal chemical toxins. Reported studies suggest that ferroptosis is linked to several skin disorders including photoaging, skin wounds, and psoriatic inflammation. Thus, ferroptosis inhibitors are of research interest for the development of interventions for skin ailments. Our group has investigated natural products for their skin protective effects. This led to the identification of cannabidiol (CBD), a nonpsychedelic phytocannabinoid, as a natural product with promising biological activities including antioxidant and anti-inflammatory effects.…”
mentioning
confidence: 99%